Sarocladium guizhouense, a new insect-associated species from Guizhou, China - Tian, Xiao-Li; Chen, Wan-Hao; Li, Dan; Chen, Lan-Ya; Zhao, Jie-Hong (Phytotaxa, 2025)
Sarocladium species often known as plant pathogens, opportunistic human pathogens, endophytes, mycoparasites and saprobes. During a survey of fungi from Southwest China, a new species, Sarocladium guizhouense was isolated from an infected scale insect. Morphological comparisons and phylogenetic analyses based on multigene datasets (ITS, LSU and TEF) support the establishment of the new species. It differs from other species by having smaller conidia, and its conidia are not arranged in a false head or chain.